Analysis of The Substitution of Coconut Shell Ash and Glass Powder in Cement Mixtures with Sikafume Additives on The Compressive Strength of Concrete - Ahda, Nu’man; Zulkarnain, Fahrizal (Jurnal Teknologi, 2024)
This research uses coconut shell ash and glass powder to replace part of the cement aims to find out the compressive strength value of concrete and also the value of water absorption. The use of coconut shell ash as much as 5%, 7% and 9% and glass powder as much as 10% of the weight of cement. And also use additive Sikafume as much as 5% of the weight of concrete. For Normal Concrete, the compressive strength value is 12.39 MPa and the water absorption value is 1%. For the compressive strength value of concrete variation BAS1 with 5% ATK is equal to 11.44 MPa and 1.35% absorption, BAS2 with 7% ATK of 10.32 MPa 1.38% absorption, BAS3 with 9% ATK of 7.50 MPa and 1.38% absorption, BAS4 with 5% ATK with 5% Sikafume of 10.32 MPa and 1.22% absorption, BAS5 with 7% ATK with 5% Sikafume of 10.32 MPa and 1.24% absorption, BAS6 with 9% ATK with 5% Sikafume of 8.82 MPa and 1.37% absorption. The optimal concrete compressive strength value is in the BAS1 variation od 11.44 MPa and the optimal  water absorption is in the BAS4 variation of 1.22%. from the results of tis study, it can be seen that the more coconut shell ash used, the lower the compressive strength of concrete and the more water absorbed. This is because coconut shell ash in fine form reacts with free lime Ca(OH)2 and water into a solid mass that is insoluble in water, namely CSH and CAH.